KONTRIBUSI JALALUDDIN AL-SUYUTI DALAM STUDI KEISLAMAN - Ahmad Mustamsikin Koiri (UIN Sayyid Ali Rahmatullah Tulungagung, 2017)
This article seeks to elaborate on the character of Jalaluddin al-Suyuti in the field of Islamic science. His great contribution in the field of Islamic studies is evident from the fruit of the pen. al-Suyuti is known as a figure who outlines the eleven fields of Islamic science which includes field of tafsir, hadith, fiqih, nahw, ma’ani, bayan, badi‘, difference of madhhab, usul, tasawwuf, tarikh (history), and adab. al-Suyuti is one of the most capable Islamic scholars, especially in the science of hadith.